“Bilik Deteksi Dini Stunting”: Inovasi Deteksi Dini Dan Edukasi Pencegahan Stunting Pada Balita Kelurahan Krembangan Utara Kota Surabaya - Arhab Nashrullah; Adhisty Mutiara Isnain; Belarmino Gaudencio De C.; Karina Dewi Anggraeni; Siti Khotimah; Shofiyatun Hasanah; Muhammad Rafly Bouty; Anita Rizki Rahmawati Asror; Zahrotun Nur Faidah; Airatul Kibtiyah; Afifah Irfa'ul Ilmiyyah; Aslin Nuroniyah Azzahra; Dwica Sri Lestari; Ahmad Athoillah; Citra Rynda Oktavia; Nazma Sheny Latifa; Asysya Ashla; Paramita Viantry (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Stunting remains a serious chronic nutrition problem in Indonesia, with a national prevalence of 19.8 percent in 2024, including in urban areas such as RW 02, Pesapen Village, Krembangan Utara, Surabaya. Most parents of children under five in this area were unfamiliar with early stunting screening and had never received education on regular monitoring of children's nutritional status. The "Bilik Dini Stunting" community service program aimed to conduct early detection of toddlers' nutritional status through anthropometric measurements (weight, height, and Mid-Upper Arm Circumference), provide education on early stunting screening, and improve parents' understanding of balanced meal portions through the "Isi Piringku" educational game. The activity was conducted on August 6, 2026, at PAUD Tunas Mekar using a participatory approach, including counseling, balanced-menu practice with food models, anthropometric measurement, and distribution of MUAC tapes, involving 9 parents/guardians, 2 teachers, and 9 PAUD students. Screening results showed no students indicated as stunted or at risk, and parents' understanding of stunting prevention and balanced nutrition improved. The program produced educational posters and an interactive "Isi Piringku" game sheet as outputs. It is concluded that integrating education, games, and growth screening effectively raises community awareness, though regular monitoring is still required.